PERGESERAN NEGATIF KONDISI EKONOMI DI KALIMANTAN TIMUR PASCA PENYEBARAN VIRUS CORONA ( COVID 19 ) - Muhammad Awaluddin (Politeknik Negeri Samarinda, 2021)
This study aims to determine the picture of economic conditions in East Kalimantan after the spread of the corona virus (Covid 19). This study uses an explanatory approach (brief overview). From observations made by researchers, it was found that the main sector that became the mainstay of East Kalimantan province, namely the mining sector, experienced a negative growth contraction. Direct contact sectors, such as the service sector and the tourism support sector, experienced a drastic decline. The Open Unemployment Rate was classified as high and several sectors experienced negative contraction as a result of the decline in community mobility in economic activities.Keywords: Economic Growth, Economic Mobility, Open Unemployment Rate